Soccer matches but not training sessions disturb cardiac-autonomic regulation during national soccer team training camps - Muñoz-López, A.; Nakamura, F.; Orellana, J. N. (Research Quarterly for Exercise and Sport, 2021)
Purpose: Heart rate variability (HRV) can be used to monitor changes in autonomic nervous system (ANS) function. Monitoring HRV via the natural log of the root-mean-square difference of successive normal RR intervals (lnRMSSD), a decrease was related to lower parasympathetic activity and a fatigued state, and an increase was related to higher parasympathetic activity and better physical conditioning. This study analyzed daily ANS function changes among professional soccer players at national team training camps during preparation for the UEFA Eurocup 2016. Method: 23 professional soccer players were distributed into two groups: First eleven (players who played more than 60 minutes per soccer match) and Reserves (the rest of the players). HRV and session training load (s-TL) were monitored. Between-group daily differences were assessed using two-way mixed repeated measures ANOVA. Results: s-TL significantly increased (p < .05) at the beginning of each camp and significantly decreased the day before the soccer match (p < .001). There was a significant time by group interaction in lnRMSSD (p = .024). Changes were found in the First eleven group from match day +1 to match day +2 (+0.523 ms, p = .003). After the soccer match, there were between-group differences (p < .05) at +24h and +72h in lnRMSSD. Conclusions: During national team training camps, ANS function was only modified 24h and 72h after playing soccer matches, in players who played a minimum of 60 minutes. This knowledge can help coaches to monitor the impact of soccer matches during training camps to detect fatigue and improve recovery.